La normativa tributaria y el pago del impuesto a la transferencia de dominio de vehículos usados en el año 2015 - Moreno Paguay, Oswaldo Patricio (2017)
Taxes have been in force since antiquity as the Estate needs them to meet the requirements of society, generating a direct link between citizens and government. From History, Economy, Politics and Society, several important events have been described, being taxation the main tool used in order to achieve strategies and measures to get improvements in the economic model of the states. To implement improvements about tax tools, Ecuador and other countries have based their experience on the nearest countries or regions. That is why in 1997, the Internal Revenue Service (IRS) has been created, changing the taxation system in Ecuador, implementing a set of legal reforms and tax regulations; technological improvements, transparency campaigns aimed to control, eradicate fraud, evasion and avoidance of taxes. It is considered as tax evasion, the use of legal means in order to avoid and minimize tax payments. Tax avoidance stops the objectives fulfillment of the Tax Administration, decreasing State revenues and reducing equity in paying taxes. This research work done in Chimborazo Province, is aimed to the gap accuracy of the 1% payment on the domain transfer of used vehicles.